Fountain, St Thomas Cathedral - Ghosh, Ayan (2023)
Detail of the Neo-Gothic fountain at St. Thomas Cathedral, designed by noted Gothic Revival architect Sir George Gilbert Scott (1811-78). Sir Cowasjee Jehangir Readymoney had a particular association with Gilbert Scott, and they collaborated on several projects, including the Convocation Hall of the University of Bombay, designed by Scott and financed by Readymoney.